Exploring the Impact of Lesson Study in Vietnamese Primary Education: Perspectives of EFL Lecturers - Le, Thanh Thao; Pham, Trut Thuy; Tran, Thi Thuy (Papanda Publisher, 2024)
This qualitative study investigates the incorporation of Lesson Study, a pedagogical approach from Japan, into Vietnamese primary education, with a specific focus on the perspectives of Vietnamese English as a Foreign Language (EFL) lecturers. These educators, though not directly involved in primary education, engage with it through various roles like teacher training and curriculum development. The research is based on in-depth interviews with nine EFL lecturers from two educational institutions in Vietnam. Employing thematic analysis, the study identifies five key themes: collaborative enhancement of teaching practices, navigating cultural and systemic challenges, improved understanding of student learning needs, professional growth and empowerment, and challenges such as resistance to change and time constraints. These themes underscore the potential of Lesson Study in fostering collaborative and reflective teaching practices, as well as professional development. However, they also highlight the obstacles imposed by traditional educational norms and practical limitations. The study emphasizes the necessity of support structures and resources for effective implementation of Lesson Study, advocating for adaptations to align with local educational contexts and cultural values. Contributing to the discourse on professional development in EFL teaching, this research underscores the importance of collaborative, reflective practices in educational innovation. Moreover, it stresses the significance of considering unique cultural and systemic elements in applying pedagogical methods like Lesson Study. Offering specific insights into its application in the Vietnamese primary education context, this study not only enhances understanding of cross-cultural educational transfer but also provides practical guidance for educators and policymakers. It paves the way for further research in diverse educational settings, expanding the international conversation on educational practices.